Can you trust the good guys? A test of two theories of reciprocity - Sebastian Fehrler; Michael Kosfeld (Verein für Socialpolitik, 2010)
The strive for social esteem is an important motive for pro-social behavior. Many people want to be seen as nice. Recent theories have suggested that the valuation of such esteem depends on the audience. In this study we look at trust and trustworthiness towards people who do or do not identify themselves with typical altruistic goals. In a trust game we observe strong discrimination against those who do but no positive discrimination of those who do not. Moreover, we find that only those second movers who identify themselves with the goals discriminate between the audiences. The last two findings cannot be explained by existing theories.
Keywords: C92; C72; D64; 330